2015
DOI: 10.1016/j.jebo.2014.12.031
|View full text |Cite
|
Sign up to set email alerts
|

Does society underestimate women? Evidence from the performance of female jockeys in horse racing

Abstract: Women are under-represented in many top jobs. We investigate whether biased beliefs about female ability - a form of ‘mistake-based discrimination’ - are partially responsible for this under-representation. We use more than 10 years of data on the performance of female jockeys in U.K. and Irish horse racing - a sport where, uniquely, men and women compete side-by-side - to evaluate the presence of such discrimination. The odds produced by the betting market provide a window onto society's beliefs about the abi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Group players assume that players in other groups behave similarly which triggers a self-reinforcing norm to maximise the group's aspirations for higher payoffs. Outside the laboratory setting, Brown and Yang (2015) show that the relative social value between men and women leads women to be underestimated by the betting system in jump racing, where, as jockeys they can compete equally. In the social setting, group membership strongly affects the individual's perception of life circumstances through peer comparison.…”
Section: Subjective Wellbeing and External Shocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Group players assume that players in other groups behave similarly which triggers a self-reinforcing norm to maximise the group's aspirations for higher payoffs. Outside the laboratory setting, Brown and Yang (2015) show that the relative social value between men and women leads women to be underestimated by the betting system in jump racing, where, as jockeys they can compete equally. In the social setting, group membership strongly affects the individual's perception of life circumstances through peer comparison.…”
Section: Subjective Wellbeing and External Shocksmentioning
confidence: 99%
“…The methodology used to estimate the determinants of subjective well-being (SWB) matters to understand its dynamics (Ferrer-i-Carbonell and Frijters 2004;Binder and Coad 2010). While OLS models in psychology and probit/logit models in economics are used on individual data, we build from recent developments in the literature around group membership (Akerlof and Kranton 2010;Goette et al 2006;Charness and Sutter 2012;Brown and Yang 2015) to assess SWB by socio-economic group. As such, group membership is expected to affect the ranking of life domains while the financial crisis is expected to change this ranking over time.…”
Section: Introductionmentioning
confidence: 99%
“…This is despite evidence that female riders are probably slightly better performers than males (Grimes and May, 1995). Brown and Yang (2015) also argue that female riders outperform their male equivalents when considering their finishing position and the starting price of the horses they ride. Early results from an MBA study in Britain (Cashmore, 2018) reveal that women accounted for just 5.2% of all 1.25 million rides between 2003 and 2016, but performed at least as well as male riders.…”
Section: Working Sportswomen In a Man’s World: Some Theoretical And Ementioning
confidence: 98%
“…Economists Brown and Yang (2015) conducted an empirical study of the relative performance of female jockeys in the UK and Ireland. Using 10 years of wagering data, they found that female jockeys won flat races 0.3 percent more often than the betting market predicted.…”
Section: The Institutional Context and Academic Literaturementioning
confidence: 99%